Variabilidade interanual dos fluxos de CO2 em uma pastagem natural no bioma Pampa brasileiro - Mergen, Alecsander (2022)
The Pampa is a biome in South America, located in the southern region of Brazil, Uruguay and part of Argentina, its vegetation is mainly composed of grass interspersed with small gallery forests and riparian forests. The complexity of this bio is due to grass diversity, mostly by C4 species coexisting with the C3 type. The use of native fields of the Pampa biome for livestock has been taking place since the 17th century, with the introduction of cattle by the Jesuits, and is seen today as the main form of conservation of the landscape of this biome. Studies carried out suggest that natural pastures can act as important sinks of atmospheric carbon dioxide (CO2), from an economic point of view, livestock productivity in the fields must be improved. In this sense, efforts have been made to maximize livestock productivity, reducing environmental impacts on the native Pampa. A management that has shown an increase in productivity is rotational management, which consists of dividing the total area into small subdivisions through which the herd will be directed one after the other, in order to maintain an amount of biomass that conserves the floristic diversity of the fields with an adequate animal load. In this work we analyze the net exchange of CO2 ecosystem (NEE) in a livestock area with rotational management in the Pampa biome in southern Brazil. For this, we used six years of data obtained through the Eddy Covariance (EC) method in an experimental area of rotational management. The ecosystem acted as a sink of atmospheric CO2, with annual accumulations in the study period ranging from -101.0 ± 5 gC m-2 ano-1 a -381.2 ± 5 gC m-2 ano-1, with an average value over 6 years of -227.1 gC m-2 year-1. The interannual variability of NEE was not related to anomalies in climatic variables or to livestock production, probably because this management system depends on forage production conditions, which in turn are interrelated with climatic conditions. These results are important to understand the dynamics of CO2 exchange and show that the Pampa biome can be an important atmospheric CO2 sink, producing quality animal protein and preserving the local fauna and flora.